2012
DOI: 10.1124/jpet.112.195339
|View full text |Cite
|
Sign up to set email alerts
|

Aryl Hydrocarbon Receptor (AHR)-Active Pharmaceuticals Are Selective AHR Modulators in MDA-MB-468 and BT474 Breast Cancer Cells

Abstract: Leflunomide, flutamide, nimodipine, mexiletine, sulindac, tranilast, 4-hydroxytamoxifen, and omeprazole are pharmaceuticals previously characterized as aryl hydrocarbon receptor (AHR) agonists in various cell lines and animal models. In this study, the eight AHR-active pharmaceuticals were investigated in highly aggressive aryl hydrocarbon (Ah)-responsive BT474 and MDA-MB-468 breast cancer cell lines, and their effects on AHR protein, CYP1A1 (protein and mRNA), CYP1B1 (mRNA), and cell migration were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
106
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(114 citation statements)
references
References 33 publications
7
106
1
Order By: Relevance
“…Confirmation of the AHR agonist/antagonist activity of the tryptophan metabolites was determined in MDA-MB-468 and MDA-MB-231 cells, which we have previously used to investigate the activities of several AHR-active pharmaceuticals (Jin et al, 2012). Figure 4A shows that the pattern of CYP1A1 induction by tryptamine was similar in both breast cancer cell lines.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Confirmation of the AHR agonist/antagonist activity of the tryptophan metabolites was determined in MDA-MB-468 and MDA-MB-231 cells, which we have previously used to investigate the activities of several AHR-active pharmaceuticals (Jin et al, 2012). Figure 4A shows that the pattern of CYP1A1 induction by tryptamine was similar in both breast cancer cell lines.…”
Section: Resultsmentioning
confidence: 92%
“…Moreover, in CaCo-2 cells we also examined the effects of 3-indoxyl sulfate, which has previously been characterized as an AHR agonist . TCDD served as a prototypical agonist, and we also compared the effects of TCDD versus the tryptophan metabolites on proteasomedependent downregulation of the AHR protein, which is observed for some (e.g., TCDD) but not all AHR ligands (Davarinos and Pollenz, 1999;Kawajiri et al, 2009;Jin et al, 2012). All the tryptophan metabolites exhibit full or partial (indole) AHR agonist activity in CaCo-2 cells and induced CYP1A1 mRNA and protein, whereas induction of CYP1B1 was highly variable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cell context-and gene-specific AhR agonist and antagonist activities of the tryptophan metabolites are not unique and have been observed for other AhR ligands including 6-methyl-1,3,8-trichlorobenzofuran, flavonoids, and pharmaceuticals (Astroff et al, 1988;Lu et al, 1996;McDougal et al, 2001;Zhou and Gasiewicz, 2003;Jin et al, 2012;Safe et al, 2012). We also observed that the AhR antagonist CH inhibited Cyp1a1 induction by TCDD and the tryptophan metabolites, indicating that CH inhibited induction of Cyp1a1 by a diverse spectrum of AhR ligands, as previously reported elsewhere (Choi et al, 2012).…”
Section: Downloaded Frommentioning
confidence: 99%